2007
DOI: 10.1017/s0007114507742691
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency and NRAMP1 polymorphisms (INT4, D543N and 3′UTR) do not contribute to severity of anaemia in tuberculosis in the Indonesian population

Abstract: Fe-deficiency anaemia is the most common cause of anaemia in developing countries. In these settings, many chronic infections, including tuberculosis (TB), are highly prevalent. Fe is an essential nutrient for both host and mycobacteria that play a pivotal role in host immunity and mycobacterial growth. A case -control study was performed in a TB-endemic region in Jakarta, Indonesia, among 378 pulmonary TB patients and 436 healthy controls from the same neighbourhood with the same socio-economic status. In a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
3
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 37 publications
(52 reference statements)
5
47
3
6
Order By: Relevance
“…It should be noted that anemia in tuberculosis is mainly inflammatory anemia (anemia of inflammation or AI). Interestingly, this AI often resolves with TB treatment as previously reported [4] [5] [9]. Also, depending on whether HIV is also present or not, resolution of anemia was reported after ART treatment in TB-HIV+ patients [10].…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…It should be noted that anemia in tuberculosis is mainly inflammatory anemia (anemia of inflammation or AI). Interestingly, this AI often resolves with TB treatment as previously reported [4] [5] [9]. Also, depending on whether HIV is also present or not, resolution of anemia was reported after ART treatment in TB-HIV+ patients [10].…”
Section: Introductionsupporting
confidence: 67%
“…Anemia of any severity was observed in more than two-third of patients (69.5%) in the current study. This is rather a common finding during TB [4] [5], with significant frequency variability, including 67% in Gambia, 63.2% in Indonesia, 37% in Ethiopia [7], or 31.9% in South Korea [4] [5] [9]. However, the anemia in the current study seems to be at the upper end of the reported frequencies.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…On the other hand, iron deficiency causes iron-deficiency anaemia with all its associated symptoms. An optimal level of iron is needed for natural immunity against the growth of pathogens [5]. Haematological abnormalities have been associated with tuberculosis infection.…”
Section: Introductionmentioning
confidence: 99%
“…This might explain, using the host-agent-environment (HAE) model, why 90% of people infected by Mycobacterium tuberculosis (Mtb) do not develop TB disease [12]. In the western and central parts of Indonesia, NRAMP1 gene polymorphism seems not to be related to TB susceptibility [13,14], though our previous study in the eastern region showed otherwise [15].…”
Section: Introductionmentioning
confidence: 99%